Evaluation of BPJS Drug Planning Controls in Regional General IFRS dr. Soehadi Prijonegoro Sragen - Tongkonoo, Mutiah; Rahmawati, Ismi; Dewi, Lucia Vita Inandha (International Journal of Science and Society, 2024)
Service in the pharmaceutical sector at hospitals is one that must be carried out in a timely and high-quality manner in order to support good service. Controlling drug supplies has a major impact on the quality of service to patients. The aim of this research is to evaluate the BPJS drug inventory control system for the planning and procurement stages with ABC, VEN, ABC-VEN, EOQ. The research design is a type of non-experimental descriptive research with retrospective data collection. The data used for the period January-December 2021. The drugs analyzed are oral drugs and the most needed drugs are included in the ABC, VEN categories so that the BPJS ABC-VEN drug group is obtained. The results of ABC analysis with a total of 464 drugs were classified into groups. Group A 19%, group B 25.4% and group 55.6%. The VEN group analysis was Vital 19.4%, Essential 77.8% and non-Essential 2.8%. Based on the results of EOQ with a total of 113 items.